2014
DOI: 10.1097/gco.0000000000000099
|View full text |Cite
|
Sign up to set email alerts
|

Precocious puberty

Abstract: Although the appropriate threshold age of onset of central puberty remains uncertain, gonadotropin-releasing hormone analog therapy is well tolerated and effective in suppressing luteinizing hormone pulses and ovarian activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 77 publications
0
27
0
3
Order By: Relevance
“…Precocious puberty (PP) currently affects 1 in 5000 children and is 10 times more common in girls [ 1 ]. Previous studies [ 2 ] have reported that the overall PP incidence continues to increase and the puberty development age has shown an advancing trend since the 19th century. Advanced progression of secondary sex characteristics occurs in children with PP leading to compromised adult height, poor social adaptability and emotional disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Precocious puberty (PP) currently affects 1 in 5000 children and is 10 times more common in girls [ 1 ]. Previous studies [ 2 ] have reported that the overall PP incidence continues to increase and the puberty development age has shown an advancing trend since the 19th century. Advanced progression of secondary sex characteristics occurs in children with PP leading to compromised adult height, poor social adaptability and emotional disorders.…”
Section: Introductionmentioning
confidence: 99%
“…In addition and related to replacing the normal-abnormal dichotomy with a depiction of puberty as a nuanced and environmentally permeable process, the model also addresses uncertainty in the scientific literature over whether it is possible to actually mark the moment of onset. Traditionally, the age of onset determines whether a young person is "officially" experiencing puberty in a normal or abnormal way (Eugster & Palmert, 2006;Carel & Leger, 2008;Neely & Crossen, 2014). Typically, ovarian puberty displayed before the age of eight is classified as "precocious puberty" (aka abnormal), and individuals are often administered several tests that may lead to the prescription of drugs that inhibit continued pubertal development (Hayes, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Precocious puberty is divided into three categories: gonadotropin dependent (central); gonadotropin independent (peripheral); and combined (central and peripheral) [6] . In a study by Cisternino et al [33] including 438 female children, the patients were diagnosed as central precocious puberty (97.7%) and peripheral precocious puberty (2.3%).…”
Section: Discussionmentioning
confidence: 99%